Multiple mutations in RNA polymerase β-subunit gene (rpoB) in Streptomyces incarnatus NRRL8089 enhance production of antiviral antibiotic sinefungin: modeling rif cluster region by density functional theory. Issue 5 (20th January 2021) - Ogawa, Saori; Shimidzu, Hitomi; Fukuda, Koji; Tsunekawa, Naoki; Hirano, Toshiyuki; Sato, Fumitoshi; Yura, Kei; Hasunuma, Tomohisa; Ochi, Kozo; Yamamoto, Michio; Sakamoto, Wataru; Hashimoto, Kentaro; et al.
ABSTRACT: Streptomyces incarnatus NRRL8089 produces the antiviral, antifungal, antiprotozoal nucleoside antibiotic sinefungin. To enhance sinefungin production, multiple mutations were introduced to the rpoB gene encoding RNA polymerase (RNAP) β-subunit at the target residues, D447, S453, H457, and R460. Sparse regression analysis using elastic-net lasso-ridge penalties on previously reported H457X mutations identified a numeric parameter set, which suggested that H457R/Y/F may cause production enhancement. H457R/R460C mutation successfully enhanced the sinefungin production by 3-fold, while other groups of mutations, such as D447G/R460C or D447G/H457Y, made moderate or even negative effects. To identify why the rif cluster residues have diverse effects on sinefungin production, an RNAP/DNA/mRNA complex model was constructed by homology modeling and molecular dynamics simulation. The 4 residues were located near the mRNA strand. Density functional theory–based calculation suggested that D447, H457, and R460 are in direct contact with ribonucleotide, and partially positive charges are induced by negatively charged chain of mRNA. Graphical Abstract: